A Classification Model Relative to Splicing for Variants of Unknown Clinical Significance: Application to the CFTR Gene. Issue 5 (5th April 2013) - Raynal, Caroline; Baux, David; Theze, Corinne; Bareil, Corinne; Taulan, Magali; Roux, Anne‐Françoise; Claustres, Mireille; Tuffery‐Giraud, Sylvie; des Georges, Marie
<x xml:space="preserve">Abstract</x> More than 1, 900 sequence variations have already been reported worldwide in the CFTR gene, including at least 20% variants of unknown clinical significance (VUCS). We built a decision tree for the classification of these VUCS, specifically focused on their consequences on splicing by performing (1) comprehensive review of literature and databases (2) familial genetics data analysis and (3) thorough in silico studies. Our method can play a full role in interpreting the results of molecular diagnosis in emergency context. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>